2017
DOI: 10.1002/jhet.2794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Study of Novel Pyrazolylthiazoles as Potential Anti‐Breast Cancer Agents

Abstract: A novel series of pyrazolylthiazole has been synthesized from the reaction of 5‐(4‐fluorophenyl)‐3‐aryl‐4,5‐dihydropyrazole‐1‐carbothioic acid amide derivatives with different reagents. The mechanism and structures of all the novel products were assured on the foundation of spectral information and elemental analyses. The antitumor activity of all the synthesized compounds was estimated versus MCF‐7 cell line. The outcomes showed that some of the tested samples revealed powerful activity against human breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This information underscores the importance of strategic structural modifications in tailoring the pharmacological properties of these compounds, shedding light on potential avenues for further drug development in the field of kinase inhibition (Scheme 30). Abbas et al 88 devised a synthetic methodology to synthesize thiazole-based pyrazolines 79a−79b as potential anticancer agents. The synthesis involved the reaction of pyrazole-1carbothioic acid amide derivatives 78 and phenacyl bromide 25 in ethanol, catalyzed by anhydrous sodium acetate.…”
Section: Morpholine-linked Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information underscores the importance of strategic structural modifications in tailoring the pharmacological properties of these compounds, shedding light on potential avenues for further drug development in the field of kinase inhibition (Scheme 30). Abbas et al 88 devised a synthetic methodology to synthesize thiazole-based pyrazolines 79a−79b as potential anticancer agents. The synthesis involved the reaction of pyrazole-1carbothioic acid amide derivatives 78 and phenacyl bromide 25 in ethanol, catalyzed by anhydrous sodium acetate.…”
Section: Morpholine-linked Hybridsmentioning
confidence: 99%
“…Abbas et al 88 devised a synthetic methodology to synthesize thiazole-based pyrazolines 79a – 79b as potential anticancer agents. The synthesis involved the reaction of pyrazole-1-carbothioic acid amide derivatives 78 and phenacyl bromide 25 in ethanol, catalyzed by anhydrous sodium acetate.…”
Section: Thiazolyl-pyrazoline Hybridsmentioning
confidence: 99%
“…Also, pyrazolylthiazoles(Scheme 10)showed anticancer activity against human malignant hepatoma HepG2, MCF-7, and human lung cancer. The outcomes showed that some of the tested samples revealed powerful activity against human breast cancer cell line (Table 6) (Abbas, et al, 2017).…”
Section: Fig (7):anticancer Pyridazine Derivativesmentioning
confidence: 99%